A versatile approach to the synthesis of glycans containing mannuronic acid residues. Issue 12 (9th March 2021) - Alex, Catherine; Visansirikul, Satsawat; Demchenko, Alexei V.
Abstract : Reported herein is a highly stereocontrolled synthesis of α or β-glycosides of mannuronic acid from glycosyl donors equipped with the 3- O -benzoyl or 3- O -picoloyl group, respectively. Abstract : Reported herein is a new method for a highly effective synthesis of β-glycosides from mannuronic acid donors equipped with the 3- O -picoloyl group. The stereocontrol of glycosylations was achieved by means of the H-bond-mediated aglycone delivery (HAD). The method was utilized for the synthesis of a tetrasaccharide linked via β-(1 → 3)-mannuronic linkages. We have also investigated 3, 6-lactonized glycosyl donors that provided moderate to high β-manno stereoselectivity in glycosylations. A method to achieve complete α-manno stereoselectivity with mannuronic acid donors equipped with 3- O -benzoyl group is also reported.